OBSERVASI METODE PENGAJARAN MENYIMAK BAHASA JEPANG DI LPK JAPAN TRAINING CENTER PEKANBARU - Maulana, Muhammad Musthafa; Basri, Merri Silvia; Budiani, Dini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
bstract: This research is a qualitative research with descriptive approach. thepurpose of this research is to describe Japanese listening teaching methods at LPKJapan Training Center Pekanbaru. the results of this research provide practicalguidance for the development of instructor training programs at LPK Training CenterPekanbaru. Instructors need to be trained to use a variety of teaching methods and tocreate an interactive and supportive learning environment. This training should includetechniques to increase learner engagement, provide constructive feedback, and usetechnology effectively in learning. Thus, LPK Training Center Pekanbaru can continueto improve the quality of Japanese listening teaching and ensure learners get an optimallearning experience. So, it can be concluded that the listening teaching methods carriedout by instructors who teach at LPK Japan Training Center Pekanbaru are quite varied,consisting of audiolingual methods, communicative approach methods, and task-basedlearning methods..Keywords: Listen to, LPK, Japan Training Center